2013
DOI: 10.2147/vhrm.s44950
|View full text |Cite
|
Sign up to set email alerts
|

The COSEHC™ Global Vascular Risk Management quality improvement program: first follow-up report

Abstract: The Global Vascular Risk Management (GVRM) Study is a 5-year prospective observational study of 87,863 patients (61% females) with hypertension and associated cardiovascular risk factors began January 1, 2010. Data are gathered electronically and cardiovascular risk is evaluated using the Consortium for Southeastern Hypertension Control™ (COSEHC™)-11 risk score. Here, we report the results obtained at the completion of 33 months since study initiation. De-identified electronic medical records of enrolled patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…Although 70% of deaths in women are attributable to modifiable risk factors such as hypertension, the question of whether antihypertensive therapy should take into consideration potential differences in mechanisms between sexes has not been answered. Women have lower blood pressure control rates (Abuful et al, 2005), they are less likely to be appropriately treated (Ferrario et al, 2013; Joyner et al, 2012; Lloyd-Jones et al, 2005a; Lloyd-Jones et al, 2005b), and data suggest that treatment efficacies differ between the two sexes (Turnbull et al, 2007; Turnbull et al, 2008a; Turnbull et al, 2008b). In an investigation of the response rates to different drug regimens, Thoenes et al (Thoenes et al, 2010) found a higher use of thiazides and beta-blockers in women.…”
Section: Introductionmentioning
confidence: 99%
“…Although 70% of deaths in women are attributable to modifiable risk factors such as hypertension, the question of whether antihypertensive therapy should take into consideration potential differences in mechanisms between sexes has not been answered. Women have lower blood pressure control rates (Abuful et al, 2005), they are less likely to be appropriately treated (Ferrario et al, 2013; Joyner et al, 2012; Lloyd-Jones et al, 2005a; Lloyd-Jones et al, 2005b), and data suggest that treatment efficacies differ between the two sexes (Turnbull et al, 2007; Turnbull et al, 2008a; Turnbull et al, 2008b). In an investigation of the response rates to different drug regimens, Thoenes et al (Thoenes et al, 2010) found a higher use of thiazides and beta-blockers in women.…”
Section: Introductionmentioning
confidence: 99%
“…Metabolic syndrome (MetS) comprises a constellation of CV risk factors that include abdominal obesity, insulin resistance, glucose intolerance, elevated blood pressure or antihypertensive drug treatment, low levels of high-density lipoprotein (HDL-C) cholesterol, and elevated triglyceride (TG) levels [6][7][8][9][10]. Abundant evidence shows that MetS predicts the development of CVD [11][12][13].…”
Section: Introductionmentioning
confidence: 99%